Introduction to Molecular Magnetism. From Transition Metals to Lanthanides By Cristiano Benelli and Dante Gatteschi. Issue 6 (8th January 2016) - McInnes, Eric J. L.
Abstract : Wiley‐VCH, Weinheim 2015. 520 pp., hardcover, € 99.00.—ISBN 978‐3527335404